Response to my critics: In defense of Kant’s aesthetic non- conceptualism - Heidemann, Dietmar H. (Con-Textos Kantianos. International Journal of Philosophy, 2020)
In this article I respond to objections that Matías Oroño, Silvia del Luján di Saanza, Pedro Stepanenko and Luciana Martínez have raised against my non-conceptualist reading of Kant’s aesthetics. The objections are both, substantial and instructive. I first sketch my non-conceptualist reading of Kant’s doctrine of judgments of taste and then turn to what I take to be the most important criticisms that these authors have put forward. Two difficulties with a non-conceptualist reading of Kant’s aesthetics seem to be central: the cognitive status of judgments of taste and the representationalist capacity of aesthetic feeling as non-conceptual mental content. I respond to these and additional objections and defend my overall non-conceptualist interpretation of Kant’s aesthetics against my critics. I argue that Kant’s aesthetics is highly relevant for the debate over whether or not Kant is a (non-)conceptualist.